MANAJEMEN EKSTRAKULIKULER DALAM MENGEMBANGKAN MINAT DAN BAKAT ANAK di TK ABA 1 BLIMBINGREJO JEPARA - Rada Najma Sa'idah Faiz Chanda (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Researcher conducted this study with the aim to know the implementation of extracurricular management to develop children's interests and talents in TK ABA 1 Blimbingrejo Jepara. Researcher used descriptive qualitative research with research subjects were students, teachers and the headmaster of TK ABA 1 Blimbingrejo Jepara. The data collection method are documentation, interview and observation. Then it is processed by interactive data analysis techniques, with four stages in analyzing, with data collection, data reduction, data presentation and drawing conclusions. According to the Minister of Education and Culture Regulation No.62 of 2014 stated that the schedule of extracurricular activities outside of study hours is under the supervision and guidance of the school. Extracurricular activities carried out at half past ten to half past eleven, the types of extracurricular activities include drum band, Iqro, coloring, dancing, playing traditional instruments, memorizing pancasila and short prayers. The results of this study show that the interests and talents of children can develop with the extracurricular management at TK ABA 1 Blimbingrejo Jepara.